2022
DOI: 10.1038/s41572-022-00406-1
|View full text |Cite|
|
Sign up to set email alerts
|

Hazardous drinking and alcohol use disorders

Abstract: in the article. Outside his federal employment, LL receives an honorarium from the UK Medical Council on Alcoholism (Editor-in-Chief for Alcohol and Alcoholism) and royalties from Routledge for a textbook. Dr. Palmer is on the Scientific Advisory Board of Vivid Genomics and is listed as an inventor on US patent US20160038559A1. MH is a member of the scientific advisory council of the Swedish Medical Products Agency, and Scientific Advisor to the Board of Health and Social Welfare; his views expressed here do n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 377 publications
1
24
0
Order By: Relevance
“…Clinicians are in high need of quick assessments that can be used to efficiently identify and refer high-risk young drinkers who are unlikely to seek or receive intervention. 12 This study uniquely begins to address this critical gap by generating empirically derived rules using baseline characteristics to predict HED frequency, which can help to inform more effective personalized intervention referral. The prediction model identified 12 rules, culled from 21 possible characteristics, in addition to intervention status.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians are in high need of quick assessments that can be used to efficiently identify and refer high-risk young drinkers who are unlikely to seek or receive intervention. 12 This study uniquely begins to address this critical gap by generating empirically derived rules using baseline characteristics to predict HED frequency, which can help to inform more effective personalized intervention referral. The prediction model identified 12 rules, culled from 21 possible characteristics, in addition to intervention status.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol abuse is a prominent risk factor contributing to the global public health burden. 1,2 Long-term alcohol consumption is associated with the development of alcohol-related liver disease (ALD), a significant cause of chronic liver diseases that affect a substantial number of individuals annually. Approximately 20-40% of ALD patients with hepatic steatosis progress to alcohol-related steatohepatitis, which often develops into hepatic fibrosis, cirrhosis, and even hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, treatment uptake in individuals with AUD is low (Tarp et al, 2022), with only 10% of individuals with AUD in high‐income countries receiving treatment, irrespective of having access to low‐cost or free treatment services (Alonso et al, 2004). Lack of problem awareness and recognition is the most frequent reason for not seeking treatment and suggests that routine monitoring in healthcare settings using a Screening, Brief‐Intervention, and Treatment (SBIRT) approach may be useful in raising awareness, catalyzing self‐directed change, and connecting individuals to more intensive treatments (Hargraves et al, 2017; MacKillop et al, 2022; Probst et al, 2015). A recent study investigating the prevalence of problem drinking recognition and its associations reported that greater problem drinking severity, poorer mental or physical health, and negative life experiences facilitated problem drinking recognition (Spanakis et al, 2022).…”
Section: Introductionmentioning
confidence: 99%